Management of Village Transfer Expenditures: A Case Study of the Regional Financial and Revenue Management Agency of East Minahasa Regency - Deo Tan Hebert Christian Tompodung; Recky H.E. Sendouw; Fitri H.Mamonto (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Objective: This study analyzes the role of the Regional Financial and Revenue Management Agency (BPKPD) in administering village transfer expenditures and identifies the inhibiting factors it faces in East Minahasa Regency, Indonesia.Methodology: A qualitative descriptive approach was employed. Data were collected through observation, in-depth interviews with nine key informants (including BPKPD officials, the Community and Village Empowerment Agency (DPMD), and village heads), and documentation. Analysis followed Miles, Huberman, and Saldana’s interactive model.Findings: Regional government agencies possess comprehensive regulatory knowledge, but village officials lack such mastery. Roles are clearly understood by all parties. However, no binding regional regulation establishes formal Standard Operating Procedures (SOPs) or time standards. Rapidly changing central government policies (e.g., the introduction of the Red-and-White Village Cooperative/KDMP) are a major hindrance. Additional obstacles include a shortage of competent village financial staff, difficult topography, and delayed issuance of the legal framework for distributing the share of Regional Tax and Levy Revenue (BHPRD).Conclusion: The administration of village transfer expenditures is hampered by the absence of standardized SOPs, frequent policy changes, and limited village apparatus competence.Suggestions: Issue a binding regulation for SOPs, provide technical guidance for village officials, accelerate the establishment of Village Cooperatives, and promptly issue the decree on revenue sharing.Keywords: Administration, Village Transfer Expenditures, Local Financial Management, Inhibiting Factors, East Minahasa. ABSTRAK Penelitian ini bertujuan untuk menganalisis peran Badan Pengelola Keuangan dan Pendapatan Daerah (BPKPD) dalam penatausahaan belanja transfer desa serta mengidentifikasi faktor-faktor penghambat yang dihadapi di Kabupaten Minahasa Timur. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi, dokumentasi, dan wawancara mendalam terhadap sembilan informan kunci yang terdiri dari pejabat BPKPD, DPMD, dan kepala desa, yang kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa meskipun pemahaman regulasi di tingkat pemerintah daerah sudah komprehensif dan pembagian peran telah dipahami dengan jelas, namun perangkat desa masih memiliki keterbatasan dalam penguasaan aturan. Selain itu, belum tersedia regulasi daerah yang mengikat terkait Standar Operasional Prosedur (SOP) formal dan standar waktu pelayanan. Penatausahaan ini juga terhambat oleh dinamika kebijakan pemerintah pusat yang berubah cepat (seperti pengenalan Koperasi Desa Merah Putih), kurangnya kompetensi staf keuangan desa, kendala topografi, serta keterlambatan regulasi Bagi Hasil Pajak dan Retribusi Daerah (BHPRD). Oleh karena itu, disarankan agar pemerintah daerah segera menerbitkan regulasi SOP yang baku, memberikan bimbingan teknis intensif bagi perangkat desa, serta mempercepat penerbitan kerangka hukum distribusi pendapatan desa. Kata Kunci: Penatausahaan, Belanja Transfer Desa, Pengelolaan Keuangan Daerah, Faktor Penghambat, Minahasa Timur.